(untitled) (Journal of Economic Research & Business Administration, 2016)
Currently, due to the increase of oil production, export growth and domestic consumption of oil and petroleum products is an issue on how to further develop their transport. A detailed study of all aspects of oil and petroleum products transportation is very important and of great practi-cal interest to develop a strategy using different means of delivery. At the beginning of the XXI century, the dynamic development of the world’s oil production was due to the expansion of international trade in crude oil and the process raised the role of pipeline transport. Oil pipelines entangled planet Earth like a spider web. Their main direction is easy to define: from the production of oil or they are sent to places of processing of oil, or to the place of loading. For this reason, the problem of transportation of oil has led to the creation of a large network of oil pipelines.